Efektivitas Breathing Exercise Pada Anak Dengan Atrial Septal Defect (ASD) - Mayangsari, Denny Novita (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Atrial Septal Defect (ASD) is a congenital heart defect that causes abnormal blood flow between the heart's atria, leading to cardiopulmonary dysfunction. This study aims to evaluate the effectiveness of breathing exercises in improving cardiopulmonary function in children with ASD. A systematic literature review (SLR) method was employed to analyze 15 studies addressing the impact of breathing exercises on the physiological and functional parameters of children with ASD. The results showed that breathing exercises significantly increased oxygen saturation, lung vital capacity, and physical activity tolerance. Additionally, there was a reduction in pulmonary artery pressure and an increase in ejection fraction, contributing to the optimization of heart function. Game-based approaches and family involvement effectively improved adherence and intervention outcomes. The implementation of breathing exercises also provided benefits in reducing pre-procedural anxiety and accelerating post-operative recovery. Thus, breathing exercises have the potential to become an effective non-pharmacological therapeutic modality in the comprehensive management of children with ASD. This study recommends developing standardized breathing exercise protocols and conducting long-term evaluations to support broader clinical implementation.